2015
DOI: 10.1002/jbm.b.33581
|View full text |Cite
|
Sign up to set email alerts
|

A pH‐responsive carboxymethyl dextran‐based conjugate as a carrier of docetaxel for cancer therapy

Abstract: Although docetaxel is available for the treatment of various cancers, its clinical applications are limited by its poor water solubility and toxicity to normal cells, resulting in severe adverse effects. In this study, we synthesized a polymeric conjugate with an acid-labile ester linkage, consisting of carboxymethyl dextran (CMD) and docetaxel (DTX), as a potential anticancer drug delivery system. The conjugate exhibited sustained release of DTX in physiological buffer (pH 7.4), whereas its release rate incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…14 A CMD-pH-DTX conjugate was synthesized with carboxymethyl dextran (CMD) and DTX through an acid-labile ester linkage, which dramatically inhibited tumor growth than parent DTX. 15 Carboxymethyl dextran covalently coupled with paclitaxel via a gly-gly-phe-gly linker (AZ10992) exhibited excellent antitumor effects than parent paclitaxel. 16 DTX was encapsulated either in the bilayer of dextran-PLGA or in folate-conjugated dextran-PLGA nanoparticles and the antitumor potency of these DTX-loaded nanoparticles outperformed parent DTX in mice.…”
Section: Introductionmentioning
confidence: 99%
“…14 A CMD-pH-DTX conjugate was synthesized with carboxymethyl dextran (CMD) and DTX through an acid-labile ester linkage, which dramatically inhibited tumor growth than parent DTX. 15 Carboxymethyl dextran covalently coupled with paclitaxel via a gly-gly-phe-gly linker (AZ10992) exhibited excellent antitumor effects than parent paclitaxel. 16 DTX was encapsulated either in the bilayer of dextran-PLGA or in folate-conjugated dextran-PLGA nanoparticles and the antitumor potency of these DTX-loaded nanoparticles outperformed parent DTX in mice.…”
Section: Introductionmentioning
confidence: 99%
“…To address this problem, DTX has been successfully encapsulated to various nanocarriers such as carboxymethyl chitosan-poly(ethyleneglycol)-NGR peptide conjugated nanoparticles [26] and carboxymethyl dextran based conjugates [24]. These DTX-loaded nanoformulations showed improved drug solubility, enhanced cell internalization and therapeutic efficacy compared to free DTX.…”
Section: Instructionmentioning
confidence: 99%
“…However, the poor solubility in aqueous media and non-ignorable toxicity to normal tissues limit its clinical application [24,25]. To address this problem, DTX has been successfully encapsulated to various nanocarriers such as carboxymethyl chitosan-poly(ethyleneglycol)-NGR peptide conjugated nanoparticles [26] and carboxymethyl dextran based conjugates [24].…”
Section: Instructionmentioning
confidence: 99%
“…These results indicated that the hydrazone linkages could be stable at physiological pH 7.4 but degrade effectively at the lower pH of endosomes and lysosomes (pH 5–6) to release the drug. In another recent report, Seung Han et al reported CMD and docetaxel (DTX) with ester linkers (Seung Han et al, 2015 ). The polymer conjugate exhibited sustained release of DTX in pH 7.4, and its release rate increased remarkably under mildly acidic conditions resembling the intracellular environment.…”
Section: Endogenous Stimuli-responsive Polymersmentioning
confidence: 99%